The diffuse component of the global solar radiation at Qena / Egypt - SHAZLY, Dr. SAYED. M. EL. (MAUSAM, 1998)
Diffuse solar radiation on horizontal surfaces is estimated at Qena / Egypt. The basic procedure is to develop relationships of the widespread use Liu & Jordan types between the daily global horizontal radiation (G) and its diffuse component (D) using measured values of these two quantities. An error analysis has been done for the results of diffuse radiation calculated using the regression models obtained in this paper and those estimated from other known ones of the Liu & Jordan type, According to statistical evaluation of the various relationships, it is seen that our models provide the best estimation of the diffuse radiation, Effect of climatic conditions was considered in the discussion.